2023
DOI: 10.3390/economies11060163
|View full text |Cite
|
Sign up to set email alerts
|

European Union Innovation Efficiency Assessment Based on Data Envelopment Analysis

Abstract: Though much attention is dedicated to the development of its research and innovation policy, the European Union constantly struggles to match the level of the strongest innovators in the world. Therefore, there is a necessity to analyze the individual efforts and conditions of the 27 member states that might determine their final innovative performance. The results of a scientific literature review showed that there is a growing interest in the usage of artificial intelligence when seeking to improve decision-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Wang et al [46] integrated economic and environmental factors within supply chains to create a sustainability indicator and proposed a supply chain greenness assessment method based on the multi-regional inputoutput model (MRIO) and DEA. Additionally, Andrijauskiene et al [47] utilized DEA to evaluate the European Union's innovation efficiency from 2000 to 2020. Notably, Kuo and Kusiak [48] demonstrated that data-driven production research has transitioned from analytical models to data-driven approaches, with manufacturing and DEA emerging as the most popular application areas for these methodologies.…”
Section: Data Envelopment Analysis Methodsmentioning
confidence: 99%
“…Wang et al [46] integrated economic and environmental factors within supply chains to create a sustainability indicator and proposed a supply chain greenness assessment method based on the multi-regional inputoutput model (MRIO) and DEA. Additionally, Andrijauskiene et al [47] utilized DEA to evaluate the European Union's innovation efficiency from 2000 to 2020. Notably, Kuo and Kusiak [48] demonstrated that data-driven production research has transitioned from analytical models to data-driven approaches, with manufacturing and DEA emerging as the most popular application areas for these methodologies.…”
Section: Data Envelopment Analysis Methodsmentioning
confidence: 99%